Dolutegravir: Clinical and Laboratory Safety in Integrase Inhibitor–Naive Patients. Issue 5 (September 2014) - Curtis, L.; Nichols, G.; Stainsby, C.; Lim, J.; Aylott, A.; Wynne, B.; Clark, A.; Bloch, M; Maechler, G.; Martin-Carpenter, L..; Raffi, F.; Min, S.
Abstract : Background: The efficacy of dolutegravir (DTG) has been demonstrated in 5 randomized studies in integrase inhibitor (INI)–naive adult populations. To date, a detailed safety review of DTG has not been provided in the literature.Objective: To describe the safety and tolerability profile of DTG in adults based on 5 randomized, controlled trials and comparison with drugs in 3 major antiretroviral (ARV) classes.Methods: Safety data from phase IIb/III/IIIb trials in ART-naive and ART-experienced, INI-naive adults were integrated.Results: In 4 ART-naive (SPRING-1, SPRING-2, SINGLE, FLAMINGO) and 1 ART-experienced, INI-naive study (SAILING), 1, 579 individuals received a DTG-containing regimen. The proportion of individuals from DTG treatment arms who withdrew due to adverse events (AEs) was low (≤2%) compared to raltegravir (RAL; 2% SPRING-2, 4% SAILING), efavirenz (EFV)–containing comparator arm (10% SINGLE), and darunavir + ritonavir (DRV/r; 4% FLAMINGO). The most frequently observed AEs (diarrhea, nausea, headache), typically grade 1 or 2 in severity, did not lead to study discontinuation. Psychiatric and nervous system disorders with DTG were comparable to RAL- and DRV/r-containing regimens and favorable to EFV-containing regimens. In hepatitis B and/or C coinfected ART-naive individuals, the incidence of transaminase elevations was lower with DTG versus RAL and EFV comparators, but was similar to DRV/r. In SAILING, transaminase elevations were more commonly observed with DTG, particularly in the setting of inadequate hepatitis B therapy or immune reconstitution. On DTG treatment, mild creatinine elevations occurred and stabilized early. Few cases of hypersensitivity reaction and/or severe rash were seen. Rates of these events were comparable to or lower than with RAL-, EFV-, and DRV/r-containing regimens.Conclusions: The safety profile for DTG 50 mg once daily in INI-naive individuals was comparable to RAL- and DRV/r-containing regimens and generally favorable compared with EFV-containing regimens.